Guy de Chauliac’s On Bloodletting in Glasgow, University Library, MS Hunter 307 (ff. 165v-166v) - Esteban-Segura, María Laura; Soriano-Jiménez, Carlos (Universidad de La Laguna, 2023)
This paper presents the edition and analysis of the text housed in Glasgow, University Library, MS Hunter 307, ff. 165v-166v, which contains a version of the treatise On Bloodletting by Guy de Chauliac, an important author of medieval surgery, and which remains unedited, to the best of our knowledge. The objectives are the following: first, to investigate the transmission of the text; second, to explore the main codicological and palaeographical features of the treatise; third, to provide the first edition of the witness and discuss its main tenets; and finally, to examine the language of the text in order to locate it geographically. The assessment of all of the above will offer a complete picture of the treatise and will help to place it in its material and cultural context.
Keywords: de Chauliac, Guy - Crítica e interpretación; GUL MS Hunter 307; Guy de Chauliac; bloodletting; medical prose; Middle English; eLALME